Antioxidant Potential of Usnea spp. Extract with Lysozyme Conjugation for the Prevention of Chronic Kidney Disease Progression - Junior, Darren; Dewi, Luh Putu Widya Amritha; Indratmo, Novea; Indrayani, Agung Wiwiek (Indonesian Journal of Pharmaceutics, 2024)
The prevalence of chronic kidney disease worldwide has been reported to increase every year with hypertension serving as the leading cause. The recommended treatment for chronic kidney disease patients with a history of hypertension is antihypertensive medications, which could cause side effects from prolonged use. Hence, the authors sought out a possible novel modality by implementing antioxidant properties from beard lichen (Usnea spp.) extract. Literature search was conducted on trusted scientific databases, including Google Scholar, PubMed, DOAJ, and Cochrane. The pathophysiology of hypertension in the progression of chronic kidney disease could mainly be attributed to the presence of inflammation and oxidative stress, which could be attenuated by the use of antioxidants. Lichens are a class of complex living organisms resulting from a symbiosis that allows them to synthesize various beneficial phytochemicals. Usnic and stictic acid derived from Usnea spp. are part of phenolic compounds that display strong antioxidant activities. In order for these antioxidants to have a focused effect on the kidneys, a kidney-targeted drug delivery system should be considered with lysozyme conjugation being the most studied method. The combination of Usnea spp. extract’s antioxidant capabilities with lysozyme conjugation could serve as a potential novel modality in the specific prevention of chronic kidney disease progression.                 Keywords: antioxidant; chronic kidney disease; lysozyme conjugation; Usnea                       spp.